Comparative Analysis of the Concept of Beauty in Linguistic Space - Almas A. Naymanbaev, Meiramkul Z. Dzhanbubekova, Anna O. Pak, Gulsara M. Aubakirova, Gulzhan S. Suleyeva,; Nabidullin, Aibolat S. (Opción, 2019)
The research objective is to study the stereotyped perception of the concept of beauty in the Chinese and Russian linguocultures. Comparative analysis of 450 Chinese understatements-allegories and 550 Russian phraseological units and proverbs was performed. As a result, there are common characteristics of synonymic units in these languages, while the differential traits also reveal similarities. In conclusion, Language is the main instrument for the formation, development and preservation (in the form of written manuscripts) of culture, because the linguistic system forms key moments of material and spiritual culture.